The Relationship of Teachers' Creativity Fostering Behaviour with 21st Century Classroom Management - Jaggil Apak; Muhamad Suhaimi Taat (2018)
This study was aimed at identifying the relationship of teachers’ creativity fostering behaviour with 21stcentury classroom management among teachers in normal daily government-aided secondary schools in Sabah, Malaysia. The non-experimental study utilised the observation method by combining several variable sampling techniques to obtain samples. Data was collected through a set of adapted questionnaires administered to 439 teachers. The data were analysed using the IBM SPSS Statistical 21.0 software. Descriptive and inferential statistics such as percentage, mean, standard deviation, t-test, and Pearson correlation were used to analyse the data to answer the research questions. Descriptive analysis teachers’ creativity fostering behaviour and 21stcentury classroom management being practised at a high level. Findings of the study also showed a significant difference in the min score of teachers’ creativity fostering behaviour and 21stcentury classroom management according to gender. Pearson correlation test indicated a moderate positive linear relationship for teachers’ creativity fostering behaviour with 21stcentury classroom management. The implications and suggestions for further study are also discussed.